Revisiting the Risk-Neutral Approach to Optimal Policyholder Behavior: A Study of Withdrawal Guarantees in Variable Annuities - Moenig, Thorsten; Bauer, Daniel (Review of Finance, 2016)
Policyholder exercise behavior presents an important risk factor for pricing Variable Annuities. However, approaches presented in the literature—building on value-maximizing strategies akin to pricing American options—do not square with observed price and exercise patterns for popular withdrawal guarantees. We show that including taxes into the valuation closes this gap between theory and practice. In particular, we develop a subjective risk-neutral valuation methodology that takes into consideration differences in the tax structure between investment opportunities. We demonstrate that accounting for tax advantages significantly affects the value of the guarantees and produces results that are in line with empirical patterns.